Decision support systems V – big data analytics for decision making : first International Conference, ICDSST 2015, Belgrade, Serbia, May 27-29, 2015, proceedings /: first International Conference, ICDSST 2015, Belgrade, Serbia, May 27-29, 2015, proceedings. (2015) - Unknown
No abstract available